The agricultural rehabilitation project = (The World Bank in Vietnam (WB), 2003)
The objectives of the project are to support Government efforts to increase rural incomes and to assist Viet Nam's transition to a market economy through assistance to key agriculture institutions serving the newly emerged smallholder sector and to rubber production. It will be the first project in the sector since 1978 and will: 1) help rehabilitate agricultural support services by providing assistance to decentralize extension in 23 provinces, to improve plant protection services including integrated pest management, and to strengthen research in three key institutes; 2) provide supervised credit to about 50,000 private smallholder farm households in 10 provinces to purchase fertilizer, improved seeds and other inputs, and for on-farm development works; 3) rehabilitate about 160,000 ha of already established rubber of high potential productivity, provide additional processing capacity and upgrade the quality of rubber being produced through construction of 5 new latex processing facilities and rehabilitation of 4 old latex facilities; and 4) provide training, and technical assistance for policy analysis and preparation of follow-up projects to give more specialized assistance to the sector.